Systems Principles, Systems Science, and the Future of Systems Engineering. Issue 1 (29th May 2019) - Rousseau, David; Calvo‐Amodio, Javier
ABSTRACT: The rise of complexity in engineered systems is radically increasing the risks in complex systems engineering projects. This rise is a challenge for systems engineering, which is still based on heuristics and not yet grounded in a general theory of systems. Such a theory is needed if systems engineering is to improve its methods, processes, and tools systematically. This article reviews ongoing initiatives to develop this foundation.